Foraging behavior of Xylocopa (Neoxylocopa) cearensis Ducke (Hymenoptera: Apidae, Xylocopini) in a population of Cuphea brachiata Koehne (Lythraceae) - Pigozzo, Camila M; Neves, Edinaldo L; Jacobi, Claudia M; Viana, Blandina F (Neotropical entomology, 2007)
An analysis of the foraging behavior of the bee Xylocopa (Neoxylocopa) cearensis Ducke among shrubs of Cuphea brachiata Koehne (Lythraceae), a key component in the Abaeté coastal sand dunes, Salvador, BA, Brazil, suggests that this bee is very important for the maintenance of the plant population, performing the pollination. This dispersal, however, is spatially restricted, so the populations in the area are likely to be highly structured genetically.